Propuesta de solución a la corrosión biogénica en alcantarillado de AASS con mortero en base a aluminato de calcio - Jarrín Sempértegui, Marcelo Fernando (2024)
Biogenic corrosion in sewage is a common problem caused by microbial activity that generates hydrogen sulfide and sulfuric acids, deteriorating concrete and mortar structures. A promising solution proposal is to use calcium aluminate (CAC)- based mortar to coat the internal surfaces of sewage systems. Calcium aluminate is a cementitious material that offers special properties such as high chemical resistance and fast setting speed, making it suitable for corrosive environments. The proposal involves applying this mortar on the internal walls of the sewer, forming a protective layer that prevents the infiltration of corrosive agents and protects the underlying structure.....